Plant-microbiome interactions under drought—insights from the molecular machinist’s toolbox - Ait-El-Mokhtar, Mohamed; Meddich, Abdelilah; Baslam, Marouane (Frontiers in Sustainable Food Systems, 2023)
Plants face numerous challenges in novel and harsh environments, including altered precipitation regimes, salinity, extreme temperatures, increased atmospheric CO2, nutrient deficiency, heavy metals, and oxygen. Drought remains a major constraint to crop productivity and meeting food demand, with the frequency, intensity, and duration of drought expected to raise in the coming century. The “cry for help” hypothesis proposes that timely recruiting of the microbiome by plants may confer benefits in stress alleviation, plant growth, fitness, and health. The root-associated microbiome harbors 10–100 times more functional genes than the host, which can significantly stimulate the metabolic and genetic potential of plant–microbiome assembly. However, cross-talk among drought and the root-associated microbes, and among the root-associated microbiome and the host-plant, is less well understood. Understanding the molecular aspect of multiple mechanisms by which microbes associate with plants during drought stress is of fundamental importance in plant biology and agriculture. In this review, we examine the progress in research on the response of plant and its microbiome assemblages and interactions to drought stress, including the impact of drought and root exudates on host resilience. We delve into the potential of ‘omics’ technologies to unravel the signaling networks underlying these interactions and the multiway interactions that occur among the host and its associated microbiome. We then discuss the shortfalls, challenges, and future research directions in this field. Overall, we argue that harnessing/manipulating the crop microbiome presents a promising strategy for improving agricultural systems in the face of global climate change.